Exploring the Meaning of Internship Experiences Among Undergraduate Students of Nonformal Education at Manado State University Using Photo Elicitation - Yudince Marinding; Caly Setiawan Caly Setiawan; Widihastuti Widihastuti (Journal of Education and Learning Research, 2026)
This study aims to explore the internship experiences of Non-Formal Education students and the meaning they construct from those experiences through the use of photo elicitation methods. The research questions focus on revealing the internship experiences of undergraduate students in the Non-Formal Education Program at Manado State University and how they interpret those experiences. The study employed a qualitative research method with a theoretical perspective grounded in the interpretivist paradigm and the epistemological foundation of constructionism. The research was conducted at a public university in central Indonesia. A total of 17 participants (6 males and 11 females) were involved in this study, selected through saturation sampling. Data collection was conducted through in-depth interviews. The findings of this study reveal three main themes or units of meaning regarding the internship experiences of undergraduate students in the Non-Formal Education Program at Manado State University: students' internship experiences, the meanings students attribute to their internships, and the continuity of competencies gained from internship experiences. These three themes are interrelated and diverse. First, the theme of students' internship experiences includes seven subthemes. Second, the theme of the meaning of internship from the students' perspective consists of nine subthemes. Third, the theme of the tendency for competency continuity includes five subthemes.